Experimental study on premixed flame acceleration in closed pipe - Mat Kiah, M. H. (Penerbit UTM Press, 2013)
An experimental study has been carried out to investigate the flame acceleration in closed pipe. A horizontal steel pipe, with 2 m long and 0.1 m diameter, giving length to diameter (L/D) ratio of 20 was used in this project. For test with 90 degree bends, the bend has a radius of 0.1 m and added a further 1 m to the length of the pipe (based on the centerline length of the segment). Ignition was affected at one end of the vessel while the other end was closed. Natural gas/oxygen mixtures were studied with equivalence ratio, Ф ranges from 0.5 to 1.8. It was demonstrated that bending pipe gave three times higher in overpressure (5.5 bars) compared to 2.0 bars of straight pipe. It is also shown that the flame speed is 63 m s-1, greater by factor of ~ 3 for explosion in bending pipe in comparison with straight pipe (23 m s-1). This is due to bending acting similar to obstacles. This mechanism could induce and create more turbulence, initiating the combustion of unburned pocket at the corner region, causing high mass burning rate and hence, increasing the flame speed.